Elevated pre‐transplant pulmonary vascular resistance is associated with early post‐transplant atrial fibrillation and mortality. (20th March 2020) - Rivinius, Rasmus; Helmschrott, Matthias; Ruhparwar, Arjang; Schmack, Bastian; Darche, Fabrice F.; Thomas, Dierk; Bruckner, Tom; Doesch, Andreas O.; Katus, Hugo A.; Ehlermann, Philipp
Abstract: Aims: Severely elevated pre‐transplant pulmonary vascular resistance (PVR) has been linked to adverse effects after heart transplantation (HTX). The impact of a moderately increased PVR before HTX on post‐transplant outcomes remains uncertain. The aim of this study was to investigate the effects of an elevated pre‐transplant PVR ≥ 300 dyn·s·cm −5 (≥3.75 Wood units) on outcomes after HTX. Methods and results: This observational retrospective single‐centre study included 561 patients receiving HTX at Heidelberg Heart Center between 1989 and 2015. Patients were stratified by degree of pre‐transplant PVR. Analyses covered demographics, post‐transplant medication, mortality and causes of death after HTX, early post‐transplant atrial fibrillation (AF), and length of the initial hospital stay after HTX. Ninety‐four patients (16.8%) had a PVR ≥ 300 dyn·s·cm −5 (≥3.75 Wood units). These patients had a higher rate of early post‐transplant AF [20.2 vs. 10.7%, difference: 9.5%, 95% confidence interval (CI): 0.9–18.1%, P = 0.01] and an increased 30 day post‐transplant mortality (25.5 vs. 6.4%, hazard ratio: 4.4, 95% CI: 2.6–7.6, P < 0.01), along with a higher percentage of death due to transplant failure (21.2 vs. 4.1%, difference: 17.1%, 95% CI: 8.7–25.5%, P < 0.01). Multivariate analysis revealed a PVR ≥ 300 dyn·s·cm −5 (≥3.75 Wood units) as a significant risk factor for increased 30 day mortality after HTX (hazard ratio: 4.4, 95% CI: 2.5–7.6, P < 0.01). Kaplan–Meier estimator showed a lower 2 year survival after HTX ( P < 0.01) in patients with a PVR ≥ 300 dyn·s·cm −5 (≥3.75 Wood units). Conclusions: Elevated pre‐transplant PVR ≥ 300 dyn·s·cm −5 (≥3.75 Wood units) is associated with early post‐transplant AF and increased mortality after HTX.